Kontribusi Usahatani Kelapa Terhadap Pendapatan Keluarga di Kecamatan Sungai Kakap Kabupaten Kubu Raya - Kusairi, Yudi; Maswadi, Maswadi; Fitrianti, Wanti (Universitas Galuh, 2024)
The community in Jeruju Besar Village has been engaged in coconut farming for generations. The income of coconut farmers' families does not solely come from coconut farming, but also from other sources of income. This is because coconut farmers harvest their coconuts every three months. As the coconut trees age and their production declines, the income of the coconut farmers also decreases. The purpose of this study is to explore the extent of income derived from coconut farming and its contribution to the family income. Data collected from the field will be organized into tables and analyzed using a descriptive quantitative method, which involves using numbers to be interpreted, analyzed, and concluded to describe the research object. All necessary information to measure the contribution of coconut farming to the overall family income is presented through simple contribution tables. The results of the study in Jeruju Besar Village concluded that the average income received by coconut farmers over three months is approximately Rp. 3,294,571.00, or equivalent to Rp. 4,640,240.00 per hectare, with the contribution percentage of coconut farming to household income being 31.03%, which falls into the low category. It is important to provide counseling on maintenance, fertilizer and pesticide assistance, as well as care for old coconut trees to farmers in order to increase coconut production.